Models of Neurodevelopmental Abnormalities in Schizophrenia - Powell, Susan B. (2010)
The neurodevelopmental hypothesis of schizophrenia asserts that the underlying pathology of schizophrenia has its roots in brain development and that these brain abnormalities do not manifest themselves until adolescence or early adulthood. Animal models based on developmental manipulations have provided insight into the vulnerability of the developing fetus and the importance of the early environment for normal maturation. These models have provided a wide range of validated approaches to answer questions regarding environmental influences on both neural and behavioral development. In an effort to better understand the developmental hypothesis of schizophrenia, animal models have been developed, which seek to model the etiology and/or the pathophysiology of schizophrenia or specific behaviors associated with the disease. Developmental models specific to schizophrenia have focused on epidemiological risk factors (e.g., prenatal viral insult, birth complications) or more heuristic models aimed at understanding the developmental neuropathology of the disease (e.g., ventral hippocampal lesions). The combined approach of behavioral and neuroanatomical evaluation of these models strengthens their utility in improving our understanding of the pathophysiology of schizophrenia and developing new treatment strategies.